Pengaruh Agresivitas Pajak, Leverage, dan Profitabilitas Terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Fernanda, Heru; Yanti, Nino Sri Purnama (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to examine Tax Aggressiveness, Leverage and Profitabilitas on Earnings Management. The dependent variable in this study is Earnings Management. While the independent variables are Tax Aggressiveness, Leverage and Profitabilitas. The population in this study are Manufacturing Companies on the Indonesia Stock Exchange in 2020-2022. The sampling method used was purposive sampling method so that 12 samples were obtained. The total number of data processed in this study was 232 data. The type of data used is secondary data. The data analysis method used in this research is multiple regression. The results of this study indicate that Tax Aggressiveness Test results from the Tax Aggressiveness obtained a t-count value of 1,519< t-table 2,69389 with a significant value of 0.139 where the significance value is > 0.05 and Leverage test results obtained a t-count value of -0,257 < t- table 2,69389 with a significant value of 0.798 where the significant value is > 0.05 so it has no significant effect on Earnings Management. While Profitabilitas test results obtained t value of -1,666 < t-table 2,69389 with a significant value of 0.105 where the significant value <0.05. so that it has no significant effect on Earnings Management